2022
DOI: 10.1088/1755-1315/1107/1/012009
|View full text |Cite
|
Sign up to set email alerts
|

Production and income dynamics of maize farmers in dryland of North Lombok Indonesia before and during the Covid-19 pandemic

Abstract: The Covid-19 pandemic has had a broad impact on several aspects of human life, one of which is the issue of food sufficiency. Due to social restrictions, the agricultural sector, which plays a role in producing food for humans, may be affected by the pandemic. These restrictions impact the availability of farm labor and the market, both agricultural inputs, and outputs. This three-year study examines the factors that influence the productivity and income of maize farmers in the dry sandy lands of Gumantar vill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…For example, similar to Sasmal (2016) and Gupta and Bhattacharya (2010), Lee et al (2011) have applied a model based on the optimal control theory to carry out sensitivity analysis for Lake Aswan, which is located between Egypt and Sudan, and evaluated the robustness of important empirical findings. Apart from that, Hitayezu et al (2016) and Jaya (2021) have presented the effectiveness of crop diversification through empirical studies conducted in other countries. Hitayezu et al (2016) have evaluated numerous cropping techniques followed by small-scale farmers in KwaZulu-Natal Midlands, South Africa.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, similar to Sasmal (2016) and Gupta and Bhattacharya (2010), Lee et al (2011) have applied a model based on the optimal control theory to carry out sensitivity analysis for Lake Aswan, which is located between Egypt and Sudan, and evaluated the robustness of important empirical findings. Apart from that, Hitayezu et al (2016) and Jaya (2021) have presented the effectiveness of crop diversification through empirical studies conducted in other countries. Hitayezu et al (2016) have evaluated numerous cropping techniques followed by small-scale farmers in KwaZulu-Natal Midlands, South Africa.…”
Section: Introductionmentioning
confidence: 99%
“…The results of their study have shown that crop diversification is typically restricted by technological variables (land and labour) and that for poorer farmers, reducing risks related to their income and production is a major driving force. Jaya (2021) has presented the importance of crop diversification as a cropping strategy for improving the livelihoods of maize farmers in the drylands of North Lombok, Indonesia. Furthermore, several studies, such as Yu et al (2019), Shen et al (2021), Zhu et al (2022) and Wang et al (2022), have addressed the issue of water conflict between upstream and downstream farmers using the game theoretical model.…”
Section: Introductionmentioning
confidence: 99%